Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41467-022-31810-6
|View full text |Cite
|
Sign up to set email alerts
|

The surfaceome of multiple myeloma cells suggests potential immunotherapeutic strategies and protein markers of drug resistance

Abstract: The myeloma surface proteome (surfaceome) determines tumor interaction with the microenvironment and serves as an emerging arena for therapeutic development. Here, we use glycoprotein capture proteomics to define the myeloma surfaceome at baseline, in drug resistance, and in response to acute drug treatment. We provide a scoring system for surface antigens and identify CCR10 as a promising target in this disease expressed widely on malignant plasma cells. We engineer proof-of-principle chimeric antigen recepto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…1d and Supplementary Dataset 2 ). While enrichment for membrane-spanning proteins for PhoX was less than DSSO, at 27.9 %, this value was still broadly consistent with our prior studies using CSC alone 7 . Combining DSSO and PhoX data, our “structural surfaceomics” approach identified 2,390 total inter-linked and intra-linked peptides on Nomo-1 cells.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1d and Supplementary Dataset 2 ). While enrichment for membrane-spanning proteins for PhoX was less than DSSO, at 27.9 %, this value was still broadly consistent with our prior studies using CSC alone 7 . Combining DSSO and PhoX data, our “structural surfaceomics” approach identified 2,390 total inter-linked and intra-linked peptides on Nomo-1 cells.…”
Section: Resultssupporting
confidence: 90%
“…The copyright holder for this preprint this version posted October 11, 2022. ; https://doi.org/10.1101/2022.10.10.511511 doi: bioRxiv preprint using CSC alone 7 . Combining DSSO and PhoX data, our "structural surfaceomics" approach identified 2,390 total inter-linked and intra-linked peptides on Nomo-1 cells.…”
Section: Development and Application Of The Structural Surfaceomics T...mentioning
confidence: 99%
See 1 more Smart Citation
“…1b ). MM patients with high levels of SLC3A2 or SLC7A5 protein expression by immunohistological staining had inferior progression-free survival 25 , and a recent study found that SLC3A2 and SLC7A5 were among the most abundant proteins on the surface of MM cells 50 . SLC3A2 may have a prominent role in plasma cells because these cells fundamentally serve as protein production factories, secreting large quantities of antibodies that require vast reserves of amino acids 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM), as a malignant proliferative disease of bone marrow plasma cells, belongs to the category of B cell lymphoma, characterized by abnormal proliferation of plasma cells with the overproduction of monoclonal immunoglobulin or light chain (M protein) [ 1 , 2 ], with no effective healing method at present. Patients still have a high possibility of recurrence after complete remission [ 3 , 4 ], so that the system of recurrence prediction is very important in the prevention and treatment of MM.…”
Section: Introductionmentioning
confidence: 99%